Go, go, planes! - Liberts, Jennifer 1970-; Yamada, Mike (New York Random House, 2021)
"A brother and sister discover all kinds of planes, from jumbo jets to toy planes, to small planes flying overhead!"--
English Stories
Ages 4-6
Grades K-1
Keywords: Airplanes -- Fiction; Siblings -- Fiction; Stories in rhyme